Composite sheet and method for producing the same
The composite sheet, featuring a porous fluororesin layer on a substrate with heat-resistant fibers and fluororesin, addresses the non-adhesive issue of fluorine resin-based sheets by enhancing water repellency and material retention.
Patent Information
- Application Number
- JP2023151416
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
Existing composite sheets using fluorine resin exhibit excellent water repellency but are highly non-adhesive, making it difficult to retain other materials on their surface.
A composite sheet comprising a substrate sheet with a heat-resistant fiber fabric and a fluororesin coating, topped with a porous fluororesin layer formed by applying a fluororesin dispersion containing a pore-forming agent and baking it.
The composite sheet achieves excellent water repellency and reduced non-adhesion, allowing it to effectively retain other materials on its surface while maintaining high water repellency.
Smart Images

Figure 2025043870000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite sheet and a method for making the composite sheet. [Background technology]
[0002] Fluoroplastics are resins with excellent heat resistance, chemical resistance, non-stickiness, etc. Sheet-shaped composite materials made by impregnating woven fabric such as glass cloth with fluoroplastics are used in a wide range of fields such as chemistry, machinery, electricity, communications, and construction.
[0003] For example, Patent Document 1 describes a composite sheet having a base fabric and a resin layer provided on at least one of the main surfaces of the base fabric. The resin layer contains a fluororesin. The composite sheet has excellent releasability and can be suitably used as a release sheet for conveyor belts for food, daily necessities, etc.
[0004] As in the above example, the surface of the composite sheet using fluororesin has excellent non-adhesive properties, making it difficult for other materials to adhere to it. In addition, such composite sheets also have excellent water repellency.
[0005] As a means for further enhancing the non-adhesiveness, there is a method of impregnating a porous member made of fluororesin with oil. For example, Patent Document 2 describes a control cable liner made by making tetrafluoroethylene resin porous and impregnating the pores with oil. By impregnating the pores with oil, it is possible to reduce the amount of sticking, especially in the initial stage, and to increase the load efficiency. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-079595 [Patent Document 2] JP 2005-282584 A Summary of the Invention [Problem to be solved by the invention]
[0007] The problem to be solved by the present invention is to provide a composite sheet that exhibits excellent water repellency and suppresses non-adhesiveness. [Means for solving the problem]
[0008] A composite sheet is provided that includes a base sheet and a porous fluororesin layer. The base sheet includes a heat-resistant fiber woven fabric and a fluororesin layer disposed on at least a portion of the heat-resistant fiber woven fabric. The porous fluororesin layer is disposed on the base sheet.
[0009] Also provided is a method for producing a composite sheet. The method includes preparing a base sheet, applying a fluororesin dispersion containing a pore-forming agent to a surface of the base sheet, and baking. The base sheet includes a heat-resistant fiber woven fabric and a fluororesin present on at least a portion of the heat-resistant fiber woven fabric. The fluororesin dispersion containing a pore-forming agent includes fluororesin particles and a pore-forming agent. Effect of the Invention
[0010] It is possible to provide a composite sheet that exhibits excellent water repellency and suppresses non-adhesiveness. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a composite sheet according to an embodiment. [Diagram 2] 1 is a scanning electron microscope image of the composite sheet produced in Example 1. [Diagram 3] 4 is a scanning electron microscope image of the composite sheet produced in Example 2. [Figure 4] 1 is a scanning electron microscope image of the composite sheet produced in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Although composite sheets containing fluororesin exhibit excellent non-adhesive properties, other materials cannot be held on the surface of the composite sheet. As a means of holding other materials, fluororesin mixed with inorganic fillers can be applied to the surface of the composite sheet. By suppressing the non-adhesive properties by mixing inorganic fillers in this way, it becomes possible to hold other materials on the surface as mentioned above, but the water repellency is inferior to that of fluororesin alone.
[0013] Hereinafter, the embodiments will be described with reference to the drawings as appropriate. Note that the same reference numerals are used to designate common components throughout the embodiments, and duplicated descriptions will be omitted. Also, each figure is a schematic diagram for explaining the embodiments and for facilitating understanding thereof, and the shapes, dimensions, ratios, etc. may differ from those of the actual device, but these can be appropriately modified in design by taking into consideration the following explanation and known techniques.
[0014] (Composite sheet) The composite sheet according to the embodiment includes a base sheet and a porous fluororesin layer provided on the base sheet. The base sheet includes a heat-resistant fiber woven fabric and a fluororesin layer on at least a portion of the heat-resistant fiber woven fabric.
[0015] The base sheet has a structure similar to that of a typical example of a conventional composite sheet using fluororesin. Therefore, although the base sheet alone has excellent water repellency, it is highly non-adhesive and cannot hold other materials.
[0016] By providing a layer having holes on the surface of the base sheet, i.e., the porous fluororesin layer, the composite sheet according to this embodiment can hold other materials. In detail, other materials can be held on the surface of the composite sheet by entering or being caught in the holes of the porous fluororesin layer. As a specific example, printing ink, oil, etc. can be held. It is desirable that holes are arranged at least on the surface of the porous fluororesin layer.
[0017] The porous fluororesin layer has pores, which makes it possible to hold different materials without using a filler. Also, by having pores on the surface, an effect similar to the lotus effect appears, improving water repellency. The porous fluororesin layer is preferably made of a single fluororesin. By having pores on the surface of a layer made of a single fluororesin, it is possible to exhibit water repellency that is greater than that derived from the fluororesin material.
[0018] An example of such a composite sheet is shown in FIG. 1. The composite sheet 1, the cross section of which is shown in FIG. 1, includes a base sheet 2 and a porous fluororesin layer 3 provided on a main surface thereof. The base sheet 2 includes a woven fabric 4, which is an example of a heat-resistant fiber woven fabric, and a fluororesin coating 5 made of a fluororesin that covers the woven fabric 4. The porous fluororesin layer 3 includes a plurality of holes 6. At least a portion of the plurality of holes 6 is located on the surface of the porous fluororesin layer 3. In the example shown in the figure, the porous fluororesin layer 3 is provided only on one main surface of the base sheet 2, but the porous fluororesin layer 3 may be provided on both main surfaces of the base sheet 2.
[0019] Hereinafter, an embodiment of the present invention will be described in detail.
[0020] The base sheet includes a heat-resistant fiber woven fabric and a fluororesin that covers at least a part of the surface of the heat-resistant fiber woven fabric. Examples of heat-resistant fiber woven fabrics include glass fiber, aramid fiber, carbon fiber, and a mixture of two or more selected from these. Glass fiber is non-flammable and has electrical insulation. On the other hand, aramid fiber has excellent strength and a certain degree of chemical resistance. Carbon fiber has superior strength, is lighter, and is conductive than glass fiber.
[0021] The heat-resistant fiber fabric may be, for example, a plain weave woven fabric of heat-resistant fibers. Alternatively, the heat-resistant fiber fabric may be a mesh cloth made by weaving rovings in which a plurality of heat-resistant fibers are bundled together. Examples of the mesh cloth include leno weave and twill weave.
[0022] Examples of the fluororesin on the heat-resistant fiber fabric in the base sheet include polytetrafluoroethylene (PTFE; tetrafluoroethylene resin), tetrafluoroethylene-perfluoroalkylvinylether copolymer resin (PFA), and tetrafluoroethylene-hexafluoropropylene copolymer resin (FEP). The type of fluororesin may be one or more. The fluororesin contained in the base material preferably contains PTFE.
[0023] In the base sheet, the fluororesin can coat the heat-resistant fiber woven fabric to form a fluororesin coating. The fluororesin coating is provided, for example, on one main surface or on both main surfaces of the heat-resistant fiber woven fabric. The thickness of the fluororesin coating can be, for example, 5 μm or more and 500 μm or less per side. The thickness of the fluororesin coating per side is preferably 10 μm or more and 300 μm or less.
[0024] The base sheet may contain a filler. The filler is desirably mixed or dispersed in the fluororesin on the heat-resistant fiber woven fabric. Examples of the filler include carbon materials, inorganic substances (titanium oxide, boron nitride, silicon oxide, zinc oxide, etc.), and various pigments. The type of filler used may be one or more types. The form of the filler is not particularly limited, and may be granular, fibrous, acicular, etc.
[0025] The porous fluororesin layer is a layer containing a fluororesin and has a plurality of holes. The porous fluororesin layer may be, for example, composed of a fluororesin. When the porous fluororesin layer contains a filler, it is preferable to keep the amount of the filler at 5% by mass or less. If the amount of the filler is 5% by mass or less, the porous fluororesin layer can maintain water repellency. As the filler to be contained in the porous fluororesin layer, the above-mentioned fillers that can be contained in the base sheet can be used. From the viewpoint of increasing water repellency, it is preferable that the porous fluororesin layer does not contain the above-mentioned filler.
[0026] It is preferable that the pores in the porous fluororesin layer are uniform in size. It is also preferable that the porous fluororesin layer contains pores in a volume ratio of 40 volume % or more and 80 volume % or less. A porous fluororesin layer containing pores in a ratio within this range is expected to have sufficient pore arrangement on the surface while maintaining strength. The pores in the porous fluororesin layer can be confirmed, for example, by observation with a scanning electron microscope.
[0027] Examples of the fluororesin contained in the porous fluororesin layer include PTFE, PFA, and FEP. The type of fluororesin may be one or more. The fluororesin contained in the porous fluororesin layer desirably contains PTFE. The fluororesin contained in the porous fluororesin layer may have the same composition as the fluororesin contained in the base sheet, or may have a different composition.
[0028] The thickness of the porous fluororesin layer may be, for example, 1 μm or more and 25 μm or less. The thickness of the porous fluororesin layer made of PTFE may be, for example, 5 μm or more and 25 μm or less, or even 15 μm or more and 20 μm or less. The thickness of the porous fluororesin layer made of PFA or FEP may be, for example, 1 μm or more and 10 μm or less, or even 2 μm or more and 5 μm or less. From the viewpoint of making the pore distribution uniform, a porous PTFE layer having a thickness of 5 μm or more is preferable as the porous fluororesin layer.
[0029] (Method of manufacturing composite sheet) The manufacturing method of the composite sheet according to the embodiment includes preparing a base sheet, applying a pore-forming agent-containing fluororesin dispersion liquid containing fluororesin particles and a pore-forming agent to the surface of the base sheet, and baking. As described above, the base sheet includes a heat-resistant fiber woven fabric and a fluororesin present on at least a part of the fabric. By forming a porous fluororesin layer on the base sheet in this manner, the composite sheet can be manufactured.
[0030] The substrate sheet can be manufactured, for example, by the following method. First, a heat-resistant fiber woven fabric is immersed in a storage tank that stores a fluororesin dispersion. The heat-resistant fiber woven fabric is removed from the fluororesin dispersion, and a coating film is formed to a predetermined thickness using a scraping roll or knife, and then dried. This process is repeated until the desired thickness is reached, and the dried coating film is baked at a temperature equal to or higher than the melting point of the fluororesin. This results in a substrate sheet having a fluororesin layer of the desired thickness provided on the heat-resistant fiber woven fabric.
[0031] The fluororesin dispersion used in the production of the base sheet can be prepared, for example, by dispersing fluororesin particles and, optionally, additives in water. As the additives, for example, the above-mentioned fillers can be used. Alternatively, a commercially available fluororesin dispersion can be used as the fluororesin dispersion.
[0032] It is preferable to use PTFE particles as the fluororesin particles. The average primary particle size of the PTFE particles is preferably in the range of 0.02 μm to 0.5 μm. More preferably, it is in the range of 0.1 μm to 0.3 μm. The average primary particle size of PTFE can be measured by observation with a transmission electron microscope.
[0033] The porous fluororesin layer can be formed, for example, by the following method.
[0034] Fluororesin particles and a pore-forming agent are dispersed in a solvent containing water to prepare a fluororesin dispersion containing the pore-forming agent. The fluororesin dispersion containing the pore-forming agent is applied to the surface of a substrate sheet, and after the coating is dried, it is baked at a temperature equal to or higher than the melting point of the fluororesin. This produces a composite sheet in which a porous fluororesin layer is formed on the substrate sheet.
[0035] The water-containing solvent may be, for example, pure water, or an aqueous solution of water to which a surfactant has been added. The pore-forming fluororesin dispersion may also be prepared, for example, by adding a pore-forming agent and, optionally, a surfactant to a commercially available fluororesin dispersion.
[0036] Examples of the pore-forming agent include particles made of acrylic resin, polyester, polystyrene, (meth)acrylic acid ester polymer, and derivatives thereof. The particle size of the pore-forming agent may be, for example, 1 μm or more. It is preferable to use a pore-forming agent with a uniform particle size.
[0037] The pore-forming agent is added in an amount of, for example, 40% to 80% by volume relative to the fluororesin particles. When PTFE particles are used as the fluororesin particles, the amount of the pore-forming agent added relative to the PTFE particles can be, for example, 25% to 70% by mass.
[0038] The surfactant can be added, for example, to improve the dispersibility of the pore-forming agent. Alternatively, a surfactant that exhibits the effect of increasing the wettability of the dispersion liquid may be added. Increasing the wettability of the dispersion liquid reduces the surface tension of the coating film obtained by applying the dispersion liquid. The reduced surface tension of the coating film makes it easier to apply multiple layers, making it easier to control the thickness of the porous fluororesin layer.
[0039] As a surfactant for improving the dispersibility of the pore-forming agent, it is preferable to use, for example, an anionic surfactant such as acrylic acid or carboxylic acid. Other anionic surfactants such as sulfosuccinic acid surfactants are difficult to obtain a dispersing effect. It is preferable to add a surfactant for improving the dispersibility of the pore-forming agent in a range that does not increase the viscosity, and it is preferable to add the surfactant in an amount of 0.5% by mass or more and 1.0% by mass or less based on the solid content.
[0040] Examples of surfactants that are highly effective in lowering the surface tension of the dispersion include nonionic surfactants such as fluorine-based and silicone-based surfactants. It is desirable to add a surfactant for lowering the surface tension in a range that does not increase the viscosity, and it is preferable to add the surfactant in an amount of 0.5% by mass or more and 1.5% by mass or less based on the solid content.
[0041] The pore-forming agent-containing fluororesin dispersion is applied to one main surface of the substrate sheet, or to both main surfaces of the substrate sheet. In addition, when applying the pore-forming agent-containing fluororesin dispersion, for example, application and drying of the dispersion are repeated until the coating film reaches a desired thickness, thereby performing recoating.
[0042] The dried final coating film is baked at a temperature equal to or higher than the melting point of the fluororesin to form a porous fluororesin layer. During baking, the pore-forming agent decomposes, forming pores in the porous fluororesin. The optionally added surfactant also decomposes during baking. Thus, a porous fluororesin consisting of simple fluororesin can be obtained.
[0043] The application of the pore-forming agent-containing fluororesin dispersion, drying, and baking can be repeated until a porous fluororesin layer of a desired thickness is obtained. EXAMPLES
[0044] Comparative Example 1 As a blank sample, a composite sheet not having a porous fluororesin layer, i.e., a base sheet, was produced as follows. A plain woven fabric of glass fiber was immersed in a PTFE dispersion, which was then dried and sintered. A commercially available PTFE dispersion was used as the PTFE dispersion. This immersion, drying and sintering process was repeated several times to produce a base sheet in which the surface of the glass fiber woven fabric was coated with PTFE.
[0045] Example 1 A base sheet was prepared in the same manner as in Comparative Example 1, and a porous fluororesin layer was formed on the surface of the base sheet to produce a composite sheet. In detail, the porous fluororesin layer was formed as follows. Powder particles made of crosslinked polymethyl methacrylate having an average particle size of 27 μm were dispersed as a pore-forming agent in an aqueous solution containing an acrylic acid-based surfactant and a silicone-based surfactant. The obtained dispersion was mixed with a commercially available PTFE dispersion so that the ratio of the pore-forming agent to the PTFE was 25:75 by volume (PTFE:pore-forming agent=25:75). The obtained PTFE dispersion containing the pore-forming agent was applied to one side of the base sheet. At this time, the amount of the dispersion applied was adjusted to 29 g / m by a scraping roll. 2 The coating was then dried and baked to form a PTFE layer and decompose the pore-forming agent and surfactant. Thus, a composite sheet having a 20 μm-thick porous fluororesin layer on the substrate sheet was obtained.
[0046] Example 2 The amount of dispersion scraped off by the scraping roll was increased to 22 g / m2. 2 A composite sheet was produced in the same manner as in Example 1, except that the temperature was adjusted to 50° C. Thus, a composite sheet having a porous fluororesin layer having a thickness of 15 μm on a base sheet was obtained.
[0047] Example 3 A PTFE dispersion containing a pore-forming agent was prepared in the same manner as in Example 1, except that the volume ratio of the pore-forming agent to the PTFE was changed to 45:55 (PTFE:pore-forming agent = 45:55). The obtained PTFE dispersion containing a pore-forming agent was applied to one side of a separately prepared substrate sheet. At this time, the amount of the dispersion applied was adjusted to 25 g / m2 using a scraping roll. 2 The coating was then dried and baked to form a PTFE layer and decompose the pore-forming agent and surfactant. Thus, a composite sheet having a 15 μm-thick porous fluororesin layer on the substrate sheet was obtained.
[0048] <Evaluation> (Scanning electron microscope observation) The composite sheet samples produced in each of Examples 1 to 3 were observed with a scanning electron microscope (SEM). SEM images of each sample are shown in Figures 2 to 4. As shown in Figure 2, in Example 1, pores are observed overall on the surface of the porous fluororesin layer, and furthermore, on the surface of the composite sheet. As shown in Figures 3 and 4, in Examples 2 and 3 as well, the pores appear to be somewhat localized in distribution, but are generally widespread over a wide area on the sheet surface.
[0049] (Contact angle measurement) For each sample of the composite sheet prepared as described above, contact angle measurement was carried out as follows. The measurement device used was an image processing contact angle meter CA-X manufactured by Kyowa Interface Science Co., Ltd. The sample was set at the measurement position of the device, and the contact angle of the sample surface was measured. The measurement conditions were as follows: Measurement method: Tangent method Atmosphere: Room temperature 23℃, relative humidity 50% Contact liquid: Pure water Measurement location: Porous fluororesin layer surface (for Comparative Example 1, substrate sheet surface) Number of measurements: 3.
[0050] The measurement results are shown in Table 1 below.
[0051] [Table 1]
[0052] As shown in Table 1, the composite sheets of Examples 1 to 3 provided with a porous fluororesin layer had a higher water contact angle than the blank sample (Comparative Example 1). It can be seen that the water repellency was improved by the porous fluororesin having pores on the surface.
[0053] (Wear test) Each sample of the composite sheet prepared as described above was subjected to an abrasion test as follows. Specifically, thrust wear tests were performed under the following conditions: Sliding method: Ring Ring material: SUS304 Ring dimensions: Outer diameter 25.6 mm x inner diameter 20 mm x height 10 mm Face-to-face contact pressure: 400 kPa Rotational speed: 200 rpm Rotation time: 3 minutes Number of tests: 3.
[0054] The test results are shown in Table 2 below.
[0055] [Table 2]
[0056] As shown in Table 2, the composite sheets of Examples 1 to 3 provided with a porous fluororesin layer had a smaller amount of wear compared to the blank sample (Comparative Example 1). It is clear that the wear resistance was improved by the porous fluororesin having pores on the surface.
[0057] (friction coefficient measurement) For each sample of the composite sheet prepared as described above, the friction coefficient was measured according to the Japanese Industrial Standard JIS K 7125:1999. For the composite sheets prepared in Examples 1 to 3, the surface of the porous fluororesin layer was used as the contact surface with the counter material. In addition, polyester nonwoven fabric (felt), PTFE tape, and a stainless steel plate made of SUS304 were used as the counter material, and the static friction coefficient and dynamic friction coefficient for each of these were measured.
[0058] The results of measuring the static friction coefficient are shown in Table 3 below, and the results of measuring the dynamic friction coefficient are shown in Table 4 below.
[0059] [Table 3]
[0060] [Table 4]
[0061] As shown in Tables 3 and 4, the composite sheets of Examples 1 to 3 provided with a porous fluororesin layer had higher values for both the static and dynamic friction coefficients when polyester felt and stainless steel plate were used as the mating material, and the composite sheets of Examples 1 to 3 had lower values when PTFE tape was used as the mating material. It can be seen that the porous fluororesin having pores on its surface improves the retention of other materials and improves the sliding properties against similar materials.
[0062] These results show that by providing a porous fluororesin, a composite sheet having both excellent water repellency and reduced non-adhesiveness can be obtained.
[0063] The present invention is not limited to the above-mentioned embodiment, and can be modified in various ways without departing from the gist of the present invention. The embodiments may be combined as appropriate, and in that case, the combined effect can be obtained. Furthermore, the above-mentioned embodiment includes various inventions, and various inventions can be extracted by combinations selected from the multiple components disclosed. For example, if the problem can be solved and the effect can be obtained even if some components are deleted from all the components shown in the embodiment, the configuration from which the components are deleted can be extracted as an invention. [Explanation of symbols]
[0064] 1...composite sheet, 2...base sheet, 3...porous fluororesin layer, 4...woven fabric, 5...fluororesin coating, 6...hole.
Claims
1. A base sheet including a heat-resistant fiber woven fabric and a fluororesin on at least a portion of the heat-resistant fiber woven fabric; a porous fluororesin layer provided on the base sheet; A composite sheet comprising:
2. 2. The composite sheet according to claim 1, wherein the porous fluororesin layer contains pores in a volume ratio of 40 volume % or more and 80 volume % or less.
3. 3. The composite sheet according to claim 1, wherein the porous fluororesin layer is made of a single fluororesin.
4. 3. The composite sheet according to claim 1, wherein the porous fluororesin layer contains polytetrafluoroethylene.
5. The composite sheet according to claim 1 or 2, wherein the fluororesin contained in the base sheet includes polytetrafluoroethylene.
6. 3. The composite sheet according to claim 1, wherein the porous fluororesin layer has a thickness of 1 μm or more and 25 μm or less.
7. Preparing a base sheet including a heat-resistant fiber woven fabric and a fluororesin on at least a portion of the heat-resistant fiber woven fabric; applying a pore-forming agent-containing fluororesin dispersion liquid containing fluororesin particles and a pore-forming agent onto a surface of the base sheet; To bake and A method for producing a composite sheet, comprising:
8. The method according to claim 7 , wherein the pore-forming agent-containing fluororesin dispersion contains the pore-forming agent in a volume ratio of 40 volume % or more and 80 volume % or less with respect to the fluororesin particles.
9. The method according to claim 7 or 8, wherein the fluororesin particles include polytetrafluoroethylene particles.
Citation Information
Patent Citations
Liner made of PTFE porous material for control cable
JP2005282584A
Composite sheet and release sheet
JP2021079595A